Pengaruh Kampanye di Akun Instagram Traveloka terhadap Online Purchase Intention - Masagus Muhammad Ibrahimsyah (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2024)
Background: The e-commerce industry in Indonesia has experienced extraordinary growth in recent years. The rapid growth of e-commerce then gave birth to e-commerce in the form of a travel agent service called Traveloka. Currently, the tagline #DontWorryNoLoss is the latest benefit offered by Traveloka to its consumers. The #DontWorryNoLoss campaign by Traveloka on Instagram is aimed at getting the target audience interested in buying their products online, which in this context is travel agent services through their application or website. Purpose: This research aims to examine the influence of the #DontWorryNoLoss campaign on the Traveloka Instagram account on online purchase intention. The background to this problem is the rapid growth of e-commerce and the role of social media in product promotion. The problem formulation focuses on how attitude toward the behavior, subjective norms, and perceived behavioral control influence consumer purchasing intentions. The theory used in this research is the Theory of Planned Behavior developed by Ajzen (1991). The aim of the research is to determine the significant influence of these three variables on the online purchase intention of Instagram followers @traveloka.id. Method: The research method used was an explanatory survey by distributing questionnaires to 81 respondents. Results: The results of this research show that there is a positive and significant influence of the #DontWorryNoLoss campaign on the online purchase intention of @traveloka.id followers.